A remarkable new species of Polochridium Gussakovskij, 1932 (Hymenoptera: Sapygidae) from China - Yue, Qi; Li, Yi-Cheng; Xu, Zai-Fu (Zootaxa, 2017)
A new species, Polochridium spinosum Yue, Li & Xu, sp. nov. (China: Hunan, Shaanxi, Henan), is described and illustrated. A key to the four Chinese species of Sapygidae is given.